Leptospira wolffii sp. nov., isolated from a human with suspected leptospirosis in Thailand - Andrew T. Slack (2018)
A single Leptospira strain (designated Khorat-H2T) was isolated from the urine of an adult male patient with suspected leptospirosis from the province of Nakornrachasima, Thailand. The isolate showed typical Leptospira motility and morphology under dark-field microscopy. Cells were 10-13 μm long and 0.2 μm in diameter, with a wavelength of 0.5 μm and an amplitude of approximately 0.3 μm. Phenotypically, strain Khorat-H2T did not grow at 13 °C but grew at 30 and 37 °C and in the presence of 8-azaguanine. Serological identification using the microscopic agglutination test revealed that strain Khorat-H2T had no cross-reaction with any recognized Leptospira serogroups. Phylogenetic analysis of the 16S rRNA gene sequence placed the novel strain within the radiation of the genus Leptospira, with sequence similarities of 88.1-97.7% to recognized Leptospira species. DNA-DNA hybridization against the type strains of the three most closely related Leptospira species was used to confirm the results of the 16S rRNA sequence analysis. The G+C content of strain Khorat-H2T was 41.8 mol%. On the basis of phenotypic, serological and phylogenetic data, strain Khorat-H2T represents a novel species of the genus Leptospira, for which the name Leptospira wolffii sp. nov. is proposed. The type strain is Khorat-H2T (=WHO LT1686T =KIT Khorat-H2T). © 2008 IUMS.